The Chemo-Sensitisation Effect Of Curcumin Against Low Dose Cisplatin On Non-Small Cell Lung Cancer (NSCLC) Stem Cells - Nazilah, Abdul Satar (2018)
Cancer stem cells (CSCs) represent a small subpopulation within a tumour that possesses the stem-like properties but are also initiating resistance towards cytotoxic agent which contribute to cancer relapse. A natural compound such as curcumin that contains high polyphenol has been found to possess chemo-sensitivity effect with an ability to sensitise the CSCs to the cytotoxic agents such as cisplatin. Therefore, the present study was designed to investigate the efficiency of curcumin as a chemo-sensitiser in lung CSCs and to analyse its inhibitory effect on CSCs activity using A549 and H2170 cell lines that belong to non-small cell lung cancer (NSCLC).